Text as a Social Network Analysis Topography And Political Communication In Indonesia - Heryono, Heri Heryono; Hamdani, Dani; Purno Wahyu, Ari (Brilliance: Research of Artificial Intelligence, 2024)
Political communication has a central role in shaping public opinion and political dynamics in Indonesia. This research aims to investigate the role of text in the context of Social Network Analysis (SNA) and political communication in Indonesia. This research combines NLP (Natural Language Processing) text analysis with SNA to understand how texts related to politics can provide insight into the relationship between political figures, political issues, and society. The research methodology involves collecting text data from various sources, such as social media, online news, blogs, and political discussion forums. The text data is then processed, analyzed and modeled with SNA analysis tools and NLP algorithms to identify relationships and communication patterns in a political context. In addition, this research also considers how the sentiments in these texts can influence the dynamics of sociopolitical networks. It is hoped that the results of this research will provide a deeper understanding of how political texts can be used as a tool for SNA analysis, with a focus on the Indonesian context. The findings of this research can be useful for political researchers, communication practitioners, and political decision makers to understand the political dynamics that are developing in the digital era. Apart from that, this research also has implications in understanding how political issues and political figures are understood and perceived by the public in political communication in Indonesia.